2021
DOI: 10.1080/23311975.2020.1869363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived service quality, website quality, and reputation on purchase intention: The mediating and moderating roles of trust and perceived risk in online shopping

Abstract: This paper aims to investigate the relationship between antecedents of trust in online shopping and purchase intention. Specifically, it examines the relationship between perceived service quality, perceived website quality, and perceived reputation, as well as the mediating role of trust in online shopping and the moderating role of perceived risk between trust and online purchase intention. An online survey was used to collect data (356 valid responses) and SmartPLS structural equation modelling (PLS-SEM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
167
5
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 71 publications
(78 reference statements)
30
167
5
23
Order By: Relevance
“…First, Harman's single factor test stated that the first factor represents only 16.18% of the variance, which is far below the acceptable threshold (50.0%) (Podsakoff et al, 2003). Second, variance inflation factor (VIF), which is called the full-collinearity approach using SmartPLS (Ali Qalati et al, 2021), requires to be ≤3 (Hair Joseph et al, 2019) (Table 3). Third, Bagozzi et al (1991) proposed that if the correlation among the constructs was >0.9, there is evidence of CMB.…”
Section: Common Methods Bias and Bartlett Spherical Testmentioning
confidence: 99%
“…First, Harman's single factor test stated that the first factor represents only 16.18% of the variance, which is far below the acceptable threshold (50.0%) (Podsakoff et al, 2003). Second, variance inflation factor (VIF), which is called the full-collinearity approach using SmartPLS (Ali Qalati et al, 2021), requires to be ≤3 (Hair Joseph et al, 2019) (Table 3). Third, Bagozzi et al (1991) proposed that if the correlation among the constructs was >0.9, there is evidence of CMB.…”
Section: Common Methods Bias and Bartlett Spherical Testmentioning
confidence: 99%
“…Prior research has proved the direct EO-SM relationship [20,44,56] and EO and SME performance [6,48], but very few studies have used SM as a mediator [78,79]. Prior studies suggest investigating the mechanisms that affect the direct EO-SME-performance link.…”
Section: Mediating Role Of Sm Adoptionmentioning
confidence: 99%
“…Similarly, [20] proposed SM as a potential mechanism that indirectly affects resources and performance, while [10] suggested that the direct EO-firm-performance link is be mediated and moderated by different constructs. Recently, [69,79,85] evidenced the mediating role of SM adoption in SMEs' context in developing countries. Thus, we argue that EO enhances SME performance indirectly by affecting SM adoption:…”
Section: Mediating Role Of Sm Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it does not meaningfully attract the consumer to make a purchase decision. Consumers' concern and insecurity about their personal information or a specific product result in negative effects on intentions (Qalati et al, 2021).…”
Section: Perceived Risk and Disadvantages Of Online Shoppingmentioning
confidence: 99%